Household bargaining with limited commitment: A practitioner's guide - Adam Hallengreen; Thomas H. Jørgensen; Annasofie M. Olesen (University of Copenhagen, Department of Economics, Center for Economic Behavior and Inequality (CEBI), 2024)
In this guide, we introduce the limited commitment model of dynamic household bargaining behavior over the life cycle. The guide is intended to make the limited commitment model more accessible to researchers who are interested in studying intra-household allocations and divorce over the life cycle. We mitigate computational challenges by providing a flexible base of code that can be customized and extended to the specific use case. The main contribution is to discuss practical implementation details of the model class, and provide guidance on how to efficiently solve limited commitment models using state-of-the-art numerical methods. The setup and solution algorithm is presented through a stylized example of dynamic consumption allocation and includes accompanying Python and C++ code used to generate all results.
Keywords: 330; Household Bargaining; limited commitment; life cycle; couples; numerical dynamic programming